Public Service Ethics in Issuing Agricultural Recommendations for Land Conversion at the Gorontalo Regency Department of Agriculture - Cindriany Pakaya; Rusli Isa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Public service in the agricultural sector is a vital instrument to maintain land resource sustainability and regional food security. In practice, issuing agricultural recommendations for land conversion often creates ethical dilemmas between economic development interests and moral responsibility to protect agricultural sustainability. This study aims to analyze the implementation of public service ethics in the process of issuing agricultural recommendations for land conversion at the Department of Agriculture, Gorontalo Regency. A qualitative descriptive approach was applied through interviews, documentation, and literature review. The findings indicate that the service process has partially adhered to ethical principles such as accountability, fairness, and transparency. However, there remains a tendency for compromise under economic and political pressure, undermining moral integrity in public service. Strengthening ethical codes, digital transparency mechanisms, and community oversight are recommended to ensure that public services operate within ethical and professional standards.